Unmasking the Triad: A Case of Severe Iron Deficiency Anemia Revealing Underlying Autoimmune Hypothyroidism and Celiac Disease - Raja Nasir Nawaz, Wafa Asjad (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
INTRODUCTION: Anemia is the most common hematologic disorder globally, with iron deficiency as the leading cause. In women of reproductive age, heavy menstrual bleeding (HMB) is a common contributor. However, underlying systemic conditions such as autoimmune disorders are often overlooked in chronic anemia cases. OBJECTIVES: The objectives of this study were to highlight the role of autoimmune diseases, particularly hypothyroidism and celiac disease, in the development of chronic anemia, and to emphasize the importance of a multidisciplinary approach when evaluating patients with unexplained or refractory anemia. By integrating perspectives from internal medicine, hematology, endocrinology, and gastroenterology, the study aims to improve early detection, accurate diagnosis, and comprehensive management of anemia related to underlying autoimmune conditions. STUDY DESIGN: Case Report STUDY SETTING: Al-Nafees Medical College and Hospital, Islamabad. CASE DESCRIPTION: A 43-year-old woman presented with symptoms of fatigue, body aches, and heavy menstrual bleeding for 3 months in the gynecology department. Initial labs confirmed severe iron deficiency anemia (Hb 6.1 g/dL), low MCV, low serum iron and ferritin, and high TIBC. Despite IV iron and tranexamic acid, no gynecological cause was identified. On referral to the medicine department, further evaluation revealed hypothyroidism (low T4, positive anti-thyroid antibodies), dyslipidemia, and fatty liver. Persistent musculoskeletal pain prompted testing for celiac disease, confirmed by positive anti-tTG antibodies. She was managed with levothyroxine, statins, calcium, and vitamin D supplements, and a strict gluten-free diet. The case highlights a complex interplay of autoimmune conditions underlying chronic anemia. CONCLUSION: Chronic iron deficiency anemia may signal underlying autoimmune overlap, as seen with coexisting hypothyroidism and celiac disease. Timely diagnosis is key, though financial barriers often delay evaluation. A high index of suspicion ensures better outcomes. KEYWORDS: Iron-deficiency anemia, autoimmune diseases, hypothyroidism, celiac disease, anti-tTG IgA